Effect of In2(SO4)3 on characteristics of Al–Li alloy MAO coating. (3rd April 2022) - Duan, Yan Fei; Liu, Ji Wei; Wang, Ping
ABSTRACT: Micro arc oxidation (MAO) coatings were prepared on the surface of 2195 Al–Li alloy by adding different amounts of indium sulphate (In2 (SO4 )3 ) into an electrolyte consisting of silicate and phosphate. The surface, cross section, phase composition, and electrochemical experiments of MAO coatings were analysed. X-ray diffraction results show that the coating was composed of γ-Al2 O3, α-Al2 O3, and In2 O3 . The results show that after adding In2 (SO4 )3, the discharge holes on the surface of the coating were more uniform and the thickness was also increased. The corrosion resistance of MAO coatings was improved by the addition of In2 (SO4 )3 .